Emerging genetic diversity of SARS-CoV-2 RNA dependent RNA polymerase (RdRp) alters its B-cell epitopes. (January 2022) - Kumar, Sushant; Kumari, Khushboo; Azad, Gajendra Kumar
Abstract: The RNA dependent RNA polymerase (RdRp) plays crucial role in virus life cycle by replicating the viral genome. The SARS-CoV-2 is an RNA virus that rapidly spread worldwide and acquired mutations. This study was carried out to identify mutations in RdRp as the SARS-CoV-2 spread in India. We compared 50217 RdRp sequences reported from India with the first reported RdRp sequence from Wuhan, China to identify 223 mutations acquired among Indian isolates. Our protein modelling study revealed that several mutants can potentially alter stability and flexibility of RdRp. We predicted the potential B cell epitopes contributed by RdRp and identified thirty-six linear continuous and twenty-five discontinuous epitopes. Among 223 RdRp mutants, 44% of them localises in the B cell epitopes region. Altogether, this study highlights the need to identify and characterize the variations in RdRp to understand the impact of these mutations on SARS-CoV-2. Highlights: SARS-CoV-2 harbours 223 mutations in its RdRp protein among Indian Isolates. Several RdRp mutants can potentially alter protein stability and flexibility. RdRp contributes to thirty-six linear continuous and twenty-five discontinuous B cell epitopes. Most of the RdRp mutants identified among Indian isolates localises (44%) in the B cell epitopes region.